2022
DOI: 10.1039/d2cp02883b
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years of molecular dynamics simulations on posttranslational modifications of proteins

Abstract: Posttranslational modifications (PTMs) are an integral component to how cells respond to perturbation. While experimental advances have enabled improved PTM identification capabilities, the same throughput for characterizing how structural changes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 285 publications
0
10
0
Order By: Relevance
“…Molecular dynamics (MD) simulations have become a widely applied computational tool to disentangle the details of nanoscopic systems relevant to a wide range of fields, from materials engineering 1,2 to fundamental biology. 3 The reason for their widespread use lies in their ability to resolve the dynamics of molecular systems at excellent time and space resolutions. Nonetheless, the fine-grained time steps of MD simulations also result in high computational costs if the processes to be observed occur at long time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have become a widely applied computational tool to disentangle the details of nanoscopic systems relevant to a wide range of fields, from materials engineering 1,2 to fundamental biology. 3 The reason for their widespread use lies in their ability to resolve the dynamics of molecular systems at excellent time and space resolutions. Nonetheless, the fine-grained time steps of MD simulations also result in high computational costs if the processes to be observed occur at long time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have become a widely-applied computational tool to disentangle the details of nanoscopic systems relevant to a wide range of fields, from materials engineering 1,2 to fundamental biology. 3 The reason for their widespread use lies in their ability to resolve the dynamics of molecular systems at excellent time and space resolutions. Nonetheless, the fine-grained time steps of MD simulations also result in high computational costs if the processes to be observed occur at long timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione transferase enzymes (GST) have been shown to catalyze protein S-glutathionylation, and the glutaredoxin Grx1 is the main responsible for protein deglutathionylation in mammalian cells, with higher activity than the thioredoxin system [9]. Despite a growing interest of scientists in unraveling regulatory mechanisms of protein glutathionylation, the amount of all atom molecular dynamics studies present in the literature remains scarce compared to other mainstream PTM such as phosphorylation [18]. In most recent computational studies, Hyslop et al reported the structural impact of SSG on the GADPH protein structure [19], Moffet et al described the SSG-induced allosteric effects in a plant kinase [20], Zhou et al investigated the effect of SSG on ATP/ADP binding to the adenine nucleotide translocator 2 protein [21], Zaffagnini et al provided clues on SSG triggered collapse of a soluble tetrameric plant protein [22], and Hameed studied the inhibition of triose-phosphate isomerase by SSG [23].…”
Section: Introductionmentioning
confidence: 99%